Microaggressions Among Online Graduate Students - Annie Hoekman; Dr. Doris Wright Carroll (Adult Education Research Conference, 2015)
Microaggressions are brief, everyday exchanges that send denigrating messages to a target group. This study analyzes empirical data taken from a graduate multicultural course taught online. The study explores the various ways interactions between adult students demonstrate forms of microaggressions.
Keywords: microaggressions; diversity; adult education